Eastern Caribbean Currency Union : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper on the Eastern Caribbean Currency Union (ECCU) underlies key features of business cycles. To obtain new measures of classical and growth cycles, simple rules were applied to date turning points in the classical business cycle, and a recently developed frequency domain filter was used to estimate the growth cycle. At the regional level, the ECCU countries are facing two shocks, id est, the depreciation of the U.S. dollar and the depreciation of the Dominican Republic's peso. The countries of the ECCU have experienced modest erosion in their price and nonprice competitiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet